Pengaruh Biourine Pada Pertumbuhan Dan Hasil Beberapa Varietas Tanaman Terong (Solanum Melongena L.) - Puspitorini, Palupi (JURNAL AGRI-TEK, 2017)
This research was conducted on 15 Januari until 15 April 2017, in Blitar. The study used a randomized complete block design with 8 treatment combinations: are A: combination of green eggplant varieties with urine dose 80 ml/plant, B: of green eggplant variety with urine dose 120 cc/plant, C: eggplant varieties green with a urine dose of 160 cc/plant, D: green eggplant varieties with urine dose 200 cc/plant, purple eggplant varieties with urine dose 80 cc/plant, F: purple eggplant varieties with urine dose 120 cc/plant, G: purple eggplant varieties with urine dose 160 cc/plant, H: purple eggplant varieties with urine dose 200 cc/plant, this research was repeated 3 times so obtained 24 unit experiment, each experiment plot consist of 15 plants. Variables observed include plant height, number of leaves, total fruit weight, fruit length and amount of fruit per plant. Giving cow urine has a significant effect on the variables of plant height, number of leaves, fruit weight, fruit length, number of fruits per plant. The best treatment is a combination of purple eggplant and 160 – 200 cc/plant of biourine.Keywords: eggplant, biourine